Mechanical-Stimuli-Driven Pseudo-Conductive Channels Along Dielectric Heterojunction Interfaces for Mechanoelectric Energy Conversion and Transmission - Seo, Byungseok (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2024 Wiley‐VCH GmbH.